More than just staffing? Assessing evidence on the complex interplay among nurse staffing, other features of organisational context and resident outcomes in long-term care: a systematic review protocol - Matthias Hoben; Megan Kennedy; Katharina Choroschun (BMJ Open)
Introduction Especially in acute care, evidence points to an association between care staffing and resident outcomes. However, this evidence is more limited in residential long-term care (LTC). Due to fundamental differences in the population of care recipients, organisational processes and staffing models, studies in acute care may not be applicable to LTC settings. We especially lack evidence on the complex interplay among nurse staffing and organisational context factors such as leadership, work culture or communication, and how these complex interactions influence resident outcomes. Our systematic review will identify and synthesise the available evidence on how nurse staffing and organisational context in residential LTC interact and how this impacts resident outcomes.Methods and analysis We will systematically search the databases MEDLINE, EMBASE, CINAHL, Scopus and PsycINFO from inception for quantitative research studies and systematically conducted reviews that statistically modelled interactions among nurse staffing and organisational context variables. We will include original studies that included nurse staffing and organisational context in LTC as independent variables, modelled interactions between these variables and described associations of these interactions with resident outcomes. Two reviewers will independently screen titles/abstracts and full texts for inclusion. They will also screen contents of key journals, publications of key authors and reference lists of all included studies. Discrepancies at any stage of the process will be resolved by consensus. Data extraction will be performed by one research team member and checked by a second team member. Two reviewers will independently assess the methodological quality of included studies using four validated checklists appropriate for different research designs. We will conduct a meta-analysis if pooling is possible. Otherwise, we will synthesise results using thematic analysis and vote counting.Ethics and dissemination Ethical approval is not required as this project does not involve primary data collection. The results of this study will be disseminated via peer-reviewed publications and conference presentation.PROSPERO Registration number CRD42021272671.